Changes in Total Protein Level in Human Female Saliva during Ovulatory Functions and Metabolic Disorders (Global Journal of Science Frontier Research, 2023)
Saliva has been studied extensively as a potential diagnostic tool over the last decade due to its ease and non-invasive accessibility along with its abundance of biomarkers, such as genetic material and proteins. The activity of protein in saliva increased during ovulation. When we monitored salivary protein activity in 40 different women volunteers during various stages of reproduction like (prepubertal, parous, non-parous, menopausal and in the metabolic disorder state diabetic condition it has been observed that highly significant (p
Keywords: saliva; total protein; pre-pubertal; parous; nonparous; menopausal and diabetic